Mapping Moodle-Based E-Learning Research in Indonesia: A Bibliometric Study of Self-Directed Learning - Dian Franssischa Kusumaningsih; Maulana Paramaditya Ananta; Durroh Nasihatul Ummah; Bambang (Galaxy: Jurnal Pendidikan MIPA dan Teknologi, 2026)
The rapid development of information and communication technology has significantly transformed educational practices, particularly through the adoption of e-learning platforms such as Moodle-based Learning Management Systems (LMS). This study aims to analyze the research trends of Moodle-based e-learning in Indonesia using a bibliometric approach. Data were collected from Google Scholar using the Publish or Perish (PoP) software, with a limitation of 500 articles published between 2018 and 2023. After a screening and refinement process, 482 articles were selected for analysis. The data were then analyzed using VOSviewer to visualize bibliometric networks, including citation patterns and keyword co-occurrence. The results show a significant increase in publications during 2020 and 2021, driven by the implementation of distance learning during the COVID-19 pandemic. Most publications are indexed in SINTA, Scopus, and conference proceedings, with several highly cited articles indicating strong academic impact. The keyword “Moodle” appears as the most dominant term, reflecting its central role in e-learning research. Furthermore, the findings reveal that Moodle-based e-learning positively contributes to learning quality, knowledge acquisition, and student satisfaction across various educational levels. In conclusion, Moodle plays a crucial role in supporting self-directed and digital learning in Indonesia. However, further research is needed to enhance its long-term effectiveness, innovation, and global research visibility.